Biology, biography and technology: review in kinship and genetics - Frois, Catarina (Reviews in Anthropology, 2009)
This review considers four recent works on in vitro fertilization; human egg donation; the relation among family, kinship and nature; genetic databases, and medical research. Assisted reproductive technology has increasingly become a tool for the artificial production of body parts. Anthropology is reformulating kinship and family theories, taking into account their relationship with biology (in the strict sense of body) and technology as primary “agents” of reproduction and the socio-cultural constitution of selves.